Intake and digestibility of dry matter in grazing river buffalo cows (Bubalus bubalis) in the cattle enterprise ?La Bayamesa?, Granma province, Cuba - Guti?rrez, Odilia; Ram?rez, B.; Cairo, Juan (Cuban Journal of Agricultural Science, 2011)
In the cattle enterprise ?La Bayamesa?, located in the Granma province, four river buffalo cows were selected randomly from a herd with the goal of estimating the intake and the digestibility of dry matter. The grazing animals were fed 300 g of Norgold and they were given in a compulsory form 20 g of chromium oxide for 17 d (twelve days of adaptation and five of collection) to determine the intake and digestibility of dry matter in grazing conditions, according to the double marking technique (chromium oxide and insoluble acid ash). The chemical and the mineral composition were determined in the feeds. The pastures were of poor quality, with crude protein contents not exceeding 8 % and total phosphorus levels lower than 0.12 %. The dry matter intake varied between the animals and ranged from 12 to 21 kg DM/animal/d in accordance with their live weights, without differences in the dry matter digestibility. The analysis of linear regression between intake and excretion of dry matter and between the contents of total ash and insoluble acid ash showed coefficients of determination of R2 = 0.97 and R2 = 0.88, respectively, for P < 0.001. It was proved that, in the conditions of this study, the buffalo river species makes a high intake of poor quality pasture, with approximate dry matter digestibility of 45 %. Key words: intake, digestibility, buffalo cows, grazing.